OPTIMIZATION OF TRANSPORT SYSTEM IN YOGYAKARTA CITY WITH VEHICLE ROUTING PROBLEM MODEL USING ALGORITHM SEQUENTIAL INSERTION - Rminugroho Ratna Sari; Dwi Lestari (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
The purposes of this study were to build a model for vehicle routing problem (VRP) for waste transportation in Yogyakarta, solve the model obtained using sequential insertion algorithm, then create an Excel Macro programming language to simulate the problem. Waste transportation conditions can be analogous to the VRP by adding intermediate facility at the end of the route, which in this case is the landfill (TPA). To determine waste transportation solved by sequential insertion algorithm. This algorithm is a method to obtain a travel route by updating the node that has not been assigned by inserting between the nodes that have been assigned. Based on 22 TPS simulated with Macro Excel, obtained 4 tours if given planning horizon length is 3 hours, and gained 3 tours if given planning horizon length is 4 hours.